Revitalisasi Bisnis Badan Usaha Milik Negara (BUMN) - Achmad Zahruddin (SOSIALITA, 2017)
Corporate function aims at the State Own Corporation to become corporation parallel to the world class corporation in supplies goods and services for its consumers. Competitive function stresses on competing capability of the State Own Corporation  infacing with its competitors within similar business sector. Regulatory function ends the era of monopolistic and protective through  an open market policy that gives access to market and equal opportunity for all business player.According to the State Own corporation position about the revitalization policy which have five (5) policy to  do : Up grade Share holder valueEffective , management , up grade operation, service and revenue Procurement System , and Restructureration and privatezation.State Own Corporation, especially the Persero is corporation having legal body for sake of profit. Although The  State Own  Corporation must have do the two function, as public service and  to find profit as a persero.